2011
DOI: 10.1007/s10641-011-9854-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in fecundity, egg case viability, gestation, and neonate size for little skates, Leucoraja erinacea, in the Gulf of Maine

Abstract: Landings of the little skate, Leucoraja erinacea, within the territorial waters of the United States are currently regulated by a federal fishery management plan (FMP). For a FMP to be effective, thorough knowledge of a species' reproductive biology is essential. Currently, little information exists on annual fecundity, egg case viability, gestation length, and neonate total length, for the little skate in the Gulf of Maine. To study these reproductive parameters, mature skates and egg cases were housed in fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…In addition, another coping mechanism could involve a shift in phenology, particularly for reproduction, to adjust to warmer temperatures (Gardner et al, 2011). However, L. erinacea has a long embryonic stage and lays eggs year-round, so temperature is not a strong factor in determining reproductive timing and behavior (Palm et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, another coping mechanism could involve a shift in phenology, particularly for reproduction, to adjust to warmer temperatures (Gardner et al, 2011). However, L. erinacea has a long embryonic stage and lays eggs year-round, so temperature is not a strong factor in determining reproductive timing and behavior (Palm et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Temperature treatments (15, 18, 20°C) were chosen to test the performance at present and projected temperatures by the end of the century IPCC, 2013;Palm et al, 2011). Each tank (150 l) was supplied with clean artificial seawater (Instant Ocean and deionized water) and had completely independent filtration, temperature and CO 2 control (i.e.…”
Section: Materials and Methods Animals And Experimental Set Upmentioning
confidence: 99%
“…Large‐scale movements of elasmobranch populations throughout their life‐cycle are often correlated with temperature ( i.e ., thermotaxis; Di Santo & Bennett, ; Economakis & Lobel, ; Hight & Lowe, ; Hunter et al, ; Matern et al, ; Vaudo & Lowe, ; Wallman & Bennett, ), which is not unsurprising given the influence of temperature on many biological processes in fishes (Magnuson et al, ; Magnuson & Destasio, ). However, one life‐stage of elasmobranchs incapable of thermotaxis is the eggs from oviparous species, which generally require a prolonged, sessile developmental period (Luer & Gilbert, ; Palm et al, ). And although increasing temperature is suspected of reducing survival of elasmobranch embryos, this has rarely been tested (Di Santo, ; Palm et al, ).…”
Section: Summary Of Experimental Treatments and Their Effect On Embrymentioning
confidence: 99%
“…These may both represent adaptive epigenetic responses to stressful conditions such as hypoxia in warmer waters. A previous study observed significant effects of temperature change on reproductive life-history traits in the closely related, little skate ( L. erinacea ) [24], suggestive of temperature-related epigenetic regulation also in this species. Finally, we saw high upregulation of transcripts associated with the determination of adult lifespan (figure 3 b ), and slight downregulation of those associated with ageing (figure 5 b ).…”
Section: Discussionmentioning
confidence: 91%
“…The effect of temperature on skate biology is poorly understood; however, from the few studies available, temperature may be important in determining the timing of growth patterns [23] and variation in reproductive life-history traits [24]. Previous studies have shown that winter skate in the southern Gulf of St Lawrence (sGSL) population appear to be an undescribed endemic, which are substantially divergent from the Scotian Shelf population in morphology (e.g.…”
Section: Introductionmentioning
confidence: 99%